To secure these rights the Declaration of Independence and constitutional interpretation - Gerber, Scott Douglas (New York Univ. Press, 1995)
From the opening chapter's bold revision of the character of the American Revolution to the closing chapter's provocative reinterpretation of many of the most famous cases in Supreme Court history, this book demonstrates the importance of approaching constitutional interpretation from more than one discipline. Indeed, Gerber's analysis reveals that the Constitution cannot be properly understood without recourse to history, political philosophy, and law
Keywords: USA -- Declaration of independence; Grondwetten; Natuurrecht; Rechtsvinding; Supreme Court (VS); Philosophie; Verfassungsrecht; Constitutional law -- United States; Natural law -- Philosophy; USA